Implementation and control of a hybrid high gain non-isolated DC-DC converter for high voltage gain applications - Tan, Wei Khuan (Nanyang Technological University, 2023)
This report describes the implementation and control of a hybrid high gain non-isolated DC-DC converter using two different non-linear controllers, namely Sliding Mode Controller and Adaptive Current-Mode Controller. The converter topology, also known as Input-Parallel Output-Series converter, was formed using two-inductor boost converter with two capacitor banks, namely, a voltage multiplier and a switched capacitor. A prototype DC-DC converter was constructed on a universal PCB for evaluation. The controllers were implemented on breadboards using op-amps. Experimental results were obtained to illustrate the features of the controllers. The various tests conducted were Start-up Transient Response, Change in Reference Voltage and Change in Load. Based on the test results, the Adaptive CMC was found to be a better controller for the DC-DC converter.